MENUJU MEKANIKA KUANTUM MODULAR - Didik Nur Huda (Faktor Exacta, 2017)
The study of quantum mechanics has been built on a Hilbert space, the complex vector space with inner product <.|.>:VxV--> C with C is a complex vector space dan  is complex numbers. Hilbert module is a generalization of Hilbert space, by changing the scalar set become ring  with certain conditions so that a Hilbert module. This ring is called the number ring. Hilbert modules that will be used to build the modular foundations of quantum mechanics.Keywords : Scalar, Rings, Hilbert Module, Quantum Mechanics